Crisis and disaster management in mines (Case study of Copiapo mine accident 2010) - Alqulaiti, Bandar Khalid (Journal of Risk and Crisis Management, 2019)
This study aims at clarifying the role of the crisis and disaster management system in the mines and development of organizational plans, the development of contact with the detainees in the mines and their organization with the world. The researcher used the descriptive analytical method, where the case of the Copiapo mine incident was studied. The results of study are: The San Jose mine incident indicates the seriousness of poor working conditions for miners during exploration, where neglect and failure to try to fix it for the best may result in disaster. The Chilean government used high efforts and efforts to rescue the workers trapped inside the mine, and there was good planning, implementation, use and innovation of the latest technologies, the results of which were the rescue of all 33 detainees. - The rescue of mine workers in Chile is a practical application that shows that dealing with crises requires human and material preparations in advance. The recommendations of study are: Increasing the awareness of mine workers and their knowledge of the culture of dealing with disaster and risk management, while providing the miners with intensive courses related to the security and safety standards in the mines and providing the staff in the mines with intensive courses in first aid, under the supervision and supervision. Provide rescue teams for mining accidents with experience in dealing with mines. Trying to carry out more than one escape exit and more than one shelter during the mining process.